Geometric analysis of a constellation with a ground target. (February 2022) - Zhang, Yujin; Bai, Shengzhou; Han, Chao
Abstract: This paper proposes a geometrical multi-satellite discontinuous-coverage analysis method for arbitrary fields that considers the J 2 perturbation. First, to calculate the single-satellite discontinuous coverage performance, the concept of single-satellite field mapping is introduced. Additionally, based on the geometric relationship between any two satellites, relative field mapping is proposed, which can transform the double-satellite coverage problem into an equivalent single-satellite coverage problem. Furthermore, by extending the concept of the relative field mapping, the constellation field mapping and its mapping regions are presented, which can be used to analytically calculate the revisit time of the constellation. The proposed method is verified by simulations under different conditions such as altitude, inclination, target latitudes, the field parameters of the sensor, sunlight, and the constellation configuration. The simulation results show that the maximum revisit time can be accurately obtained and intuitively displayed with the proposed method, which provides a valuable reference for Earth observation constellation design. Highlights: The analytical constellation field mapping with translation property is presented for the first time. The proposed constellation field mapping is time-invariant and suitable for any field of view. The discontinuous coverage can be obtained rapidly, and the sunlight constraint is considered. Other characteristics of the constellation coverage are obtained through this analysis approach.